Retinal small vessel narrowing in women with gestational diabetes, pregnancy-associated hypertension, or small-for-gestational age babies - Phillipos, Joseph; Luong, Thao Vi; Chang, Deborah; Varadarajan, Suresh; Howat, Paul; Hodgson, Lauren; Colville, Deb; Savige, Judy (Frontiers in Medicine, 2023)
Background Gestational diabetes, pregnancy-associated hypertension and small-for-gestational age babies are all associated with impaired placental vascularisation. This study compared the effects of these conditions the systemic small vessel calibre that was examined in the retina. Methods This was a cross-sectional observational study of consecutive pregnant women recruited from an antenatal clinic. Participants underwent a Glucose Tolerance Test, BP measurements, and were examined for small-for-gestational age babies as per national guidelines. They also underwent retinal photography with a non-mydriatic camera, and vessel calibres were measured with a validated semi-quantitative system at a retinal grading centre. Some participants also underwent testing of retinal vascular responsiveness to a flickering light. Results Women with gestational diabetes (n = 68) had a higher mean arterial pressure (85 ± 9 mm Hg) than normal pregnant women (n = 27, 80 ± 8 mmHg, p = 0.01). They also had smaller mean retinal arteriole (147.5 ± 13.6 μm and 159.7 ± 6.7 μm respectively, p < 0.01) and venular calibre (221.0 ± 13.4 μm and 232.8 ± 20.1 μm respectively, p < 0.01) than normal. However their babies’ mean birth weights were not different from normal (3,311 ± 558 g and 3,401 ± 600 g respectively, p = 0.48). They also demonstrated a trend to reduced retinal arteriolar dilatation (3.5 ± 1.3%, n = 23) in response to vasodilatory stimuli (4.4 ± 1.8%) (n = 11) (p = 0.08) consistent with endothelial dysfunction. Women with pregnancy-associated hypertension (n = 35) had a higher mean arterial pressure (101 ± 12 mm Hg, p < 0.01), a smaller mean retinal arteriolar calibre (139.9 ± 10.6 μm, p < 0.0001), and a lower baby mean birth weight than for normal pregnancies (3,095 ± 443 g, p = 0.02). Likewise, women with small-for-gestational age babies (n = 31) had a higher mean arterial pressure (89 ± 19 mm Hg, p = 0.03), a smaller mean retinal arteriolar calibre (141.6 ± 12.8 μm, p < 0.01) and a lower baby mean birth weight than for normal pregnancies (2,468 ± 324 g, p < 0.0001). Conclusion Mean retinal arterial calibre was reduced in women with gestational diabetes, pregnancy-associated hypertension or small-for-gestational age babies. The reduction in calibre was greatest in pregnancy-associated hypertension and small-for-gestational age babies. Systemic arteriole narrowing may contribute to the pathogenesis of placental vascular dysfunction in these conditions.